Effective salvage of acute massive uterine bleeding using intrauterine balloon tamponade in a uterine adenomyosis patient on dienogest. Issue 3 (25th September 2012) - Nishino, Kimihiro; Hayashi, Kazumasa; Chaya, Jyunya; Kato, Noriko; Yamamuro, Osamu
Abstract: We present the case of a 37‐year‐old nulliparous woman in whom acute massive uterine bleeding during dienogest therapy was successfully treated using intrauterine balloon tamponade. Abnormal uterine bleeding and several cases of profuse bleeding causing severe anemia in association with dienogest therapy have been reported, but this is the first reported case involving hypovolemic shock. While successful control of postpartum hemorrhage with intrauterine balloon tamponade has been well described, applications for non‐obstetric bleeding, particularly in the presence of underlying diseases, such as adenomyosis, have only rarely been reported. This procedure can be easily, promptly, and safely implemented without analgesia, anesthesia, or laparotomy; it can be used with a minimally dilated external cervical os or narrow uterine cavity; and it can preserve fertility.